Characterization of Taxable Units and Tax Bases under Schedule ‘C’ of the Federal Income Tax Proclamation of Ethiopia: A Commentary - Chane, Gizachew Silesh; Addis, Belete (Bahir Dar University Journal of Law, 2022)
Schedule ‘C’ is the third income tax schedule incorporated under the Federal Income Tax Proclamation of Ethiopia. The Schedule deals with business income taxation. Though the Schedule is entangled with several concerns, this work is restricted to issues related to the characterization of its taxable units and tax bases. As a commentary, it intends to serve as a guidance to understand the taxable units and tax bases of the Schedule. To accomplish this, the work used desktop research method and analyzed the relevant legislation, literature and cassation decisions. In examining how taxable units and tax bases are characterized under Schedule ‘C’, the work considers the areas of developments made by the current income tax regime such as the incorporation of provisions with clear income sources subject to the Schedule. Most importantly, the work tries to identify gaps (with potential administrative difficulties) that need consideration such as characterization tensions with other income tax schedule of the Proclamation and provisions that lack clarity. It also questioned the appropriateness of the inclusion of some entities (notably partnerships) as taxable units of the Schedule and it provides arguments to seek the attention of the concerned organs regarding the issues involved. Issuance of supplementary directives and advance rulings, the need to take relevant lessons from the experience of other jurisdictions and reconsidering some of the existing characterization are among the solutions the work recommends.